Legal Pluralism and Social Control: An Empirical Study of Adultery Law Reform - Muhamad Aminulloh; Nayla Zhafirah; Radif Khotamir Rusli (JURNAL ILMIAH GEMA PERENCANA, 2025)
Significant changes have been made to several criminal provisions with the ratification of the 2023 Criminal Code (KUHP), including an expanded definition of the crime of adultery. These modifications have generated diverse social reactions, particularly regarding potential violations of fundamental human rights and gender inequality in their implementation. This study aims to empirically investigate the impact of these new provisions on society in several regions of Indonesia. A qualitative methodology was used, focusing on appropriate feminist and human rights perspectives. Data collection techniques included documentation, observation, and public perception. Based on the research findings, the 2023 Criminal Code provisions on adultery have the potential to be used as a tool of social control, particularly against women, and to criminalize private behavior. This is interesting because the impact of their implementation in the field demonstrates inequality in legal treatment and a lack of understanding of the principles of human rights and gender justice. Theoretically, this study contributes to the fields of criminal law and sociological law while also assisting in the evaluation of public policy and the defense of fundamental human rights. Therefore, it is recommended that these provisions be evaluated to ensure they align with constitutional values, respect privacy, and protect vulnerable groups.